QUANTIZATION OF DISSIPATIVE SYSTEMS WITH SECOND-ORDER LAGRANGIAN - Jarab’ah, Ola A.; Hasan, Eyad H.; Nawafleh, Khaled I. (European Scientific Journal, ESJ, 2014)
This paper examined dissipative systems with second order Lagrangian in the framework of the Hamilton-Jacobi method. The principal function is determined using the method of separation of variables in the same manner as for regular time-independent Lagrangian. The equations of motions are obtained from the action function. By finding the action function, the wave function can be constructed and the quantization has been carried out using the WKB approximation. One example is given to illustrate our formalism.